Managing Climate Change Refugia for Climate Adaptation - Morelli, Toni Lyn; Daly, Christopher; Dobrowski, Solomon Z.; Dulen, Deanna M.; Ebersole, Joseph L.; Jackson, Stephen T.; Lundquist, Jessica D.; Millar, Constance I.; Maher, Sean P.; Monahan, William B.; Nydick, Koren R.; Redmond, Kelly T.; et al. (PloS one, 2016)
Refugia have long been studied from paleontological and biogeographical perspectives to understand how populations persisted during past periods of unfavorable climate. Recently, researchers have applied the idea to contemporary landscapes to identify climate change refugia, here defined as areas relatively buffered from contemporary climate change over time that enable persistence of valued physical, ecological, and socio-cultural resources. We differentiate historical and contemporary views, and characterize physical and ecological processes that create and maintain climate change refugia. We then delineate how refugia can fit into existing decision support frameworks for climate adaptation and describe seven steps for managing them. Finally, we identify challenges and opportunities for operationalizing the concept of climate change refugia. Managing climate change refugia can be an important option for conservation in the face of ongoing climate change.